Effect of storage time on physiochemical and sensory properties of Karadi sheep milk yoghurt - Ibrahim, Kocher Jamal; Al-Saadi, Jasim Mohammed Salah (Sulaimani Journal for Pure and Applied Sciences, 2018)
The composition of local sheep milk showed that it contained high total solids, which was 16.8%. Beside, this milk also marked by its higher ratio of total protein and fat, that were 5.3 and 6.4%, respectively. Viscosity of sheep milk yoghurt after one day and 28 days of storage at 5° C was higher than the viscosity of cow milk yoghurt. Spontaneous whey separation from cow's milk yoghurt and sheep's milk yoghurt were 3.6 and 0.3 ml after one day of production, respectively. These values were increased with the progress of storage to 4.5 and 1.5 ml after 28 days of storage at 5 °C for cow’s milk yoghurt and sheep milk yoghurt, respectively. Water holding capacity in sheep's milk yoghurt was higher than cow milk yoghurt during 28 days of storage at 5 °C. Hardness at the first day of storage, were 52 and 70 g for local sheep milk yoghurt and cow milk yoghurt, respectively. These values increased gradually to 58.5 and 85 g after 28 days of storage at 5 ° C for local sheep milk yoghurt and cow milk yoghurt, respectively. The total degrees of sensory evaluation of yoghurt produced from local sheep's milk were higher than the degrees of cow milk yoghurt during the storage for 28 days at 5°
Keywords: Yoghurt; Karadi sheep milk Physiochemical properties; Sensory properties